AESTHETIC FORM OF ANGGUK PUTRI DANCE PERFORMANCE IN PAGUYUBAN ARUM DALU VILLAGE SENTOLO KULON PROGO DISTRICT SPECIAL REGION OF YOGYAKARTA - Koliliyah, Nurul (Sembadra, Journal of Arts and Education Studies, 2020)
The Angguk Putri dance was inspired by Dutch soldiers who colonized the region of Yogyakarta. This study aimed to describe the aesthetics of the Angguk Putri dance performance in the Arum Dalu Society in Sentolo Village, Daerah Istimewa Yogyakarta. This study used descriptive qualitative methods with an Ethic and Emic approach. Data collection techniques used observation, interviews, and documentation. Data validity used triangulation, while data analysis used data reduction, data presentation, and drawing conclusions. The results showed that the aesthetics of Angguk Putri dance performance can be seen from the patterns and elements of performance. The patterns consist of opening, core, and closing greetings. The elements of the performance consist of the art (dance), artist, and artistics. Elements of dance includes movements, accompaniment, make up and costumes, and property. The dancers have an attraction in body postures, skill and movement techniques, and the expression. The artistics elements include stages, lighting, and sound system. Each element has aesthetic values that affects each other. To discover the aesthetics of the performance of the Angguk Putri Dance, can only be seen when we watch the performance in full. This study only discusses the value of beauty in the elements of the performance used, thus providing opportunities for other researchers to study the Angguk Putri Dance from another perspective. Keywords: Form, Aesthetics of performance, Angguk Putri Dance